2011
DOI: 10.2337/dc11-0338
|View full text |Cite|
|
Sign up to set email alerts
|

Nuts as a Replacement for Carbohydrates in the Diabetic Diet

Abstract: OBJECTIVEFat intake, especially monounsaturated fatty acid (MUFA), has been liberalized in diabetic diets to preserve HDL cholesterol and improve glycemic control, yet the exact sources have not been clearly defined. Therefore, we assessed the effect of mixed nut consumption as a source of vegetable fat on serum lipids and HbA1c in type 2 diabetes.RESEARCH DESIGN AND METHODSA total of 117 type 2 diabetic subjects were randomized to one of three treatments for 3 months. Supplements were provided at 475 kcal per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
88
1
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 105 publications
(94 citation statements)
references
References 22 publications
(25 reference statements)
3
88
1
1
Order By: Relevance
“…Studies have shown that a healthy diet combined with pistachios, due to its compounds, has positive effects on glycemic control, blood pressure, and obesity in patients with diabetes (27). The substitution of carbohydrates with unsaturated fatty acids is a recognized therapeutic strategy in the treatment of diabetes (39). Therefore, a diet that contains a certain amount of pistachio can improve diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that a healthy diet combined with pistachios, due to its compounds, has positive effects on glycemic control, blood pressure, and obesity in patients with diabetes (27). The substitution of carbohydrates with unsaturated fatty acids is a recognized therapeutic strategy in the treatment of diabetes (39). Therefore, a diet that contains a certain amount of pistachio can improve diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Baseline exercise routine was recorded and any subsequent change noted. The study conformed to the same general principles as other studies of this duration run from the center (16).…”
Section: Protocolmentioning
confidence: 94%
“…However, because of a larger-than-expected dropout at the start and to capture smaller effect sizes seen in our more-recent studies, participant recruitment numbers were increased to 140 (16,25). On the basis of data from a 12-week study in type 2 diabetes (16) …”
Section: Statistical Analysesmentioning
confidence: 99%
“…Otro estudio de intervención a pacientes diabéticos a quienes se les dio durante 12 semanas un mix de nueces, almendras, pistachos, pacanas, avellanas, macadamias y castañas de caju (75 g/día), todos buenas fuentes de MUFAS y fibra dietaria, mostró una reducción significativa de la HbA1c frente al grupo control (26), resultado similar a lo realizado en otra intervención en diabéticos con maní (27). Por el contrario el consumo de poliinsaturados de la familia omega 3 no presenta efectos sobre la HbA1c tal como lo muestra el meta análisis realizado por Hartweg y cols.…”
Section: Discussionunclassified